Porównawcza analiza cykli gospodarczych w kapitalizmie i socjalizmie - Balicki, Władysław (Wydział Prawa i Administracji UAM, 1984)
A summary of features common, and separately of those quite distinct to those systems is a point of departure for further study. The first group consists of economic structure, level of technology economic dualism (there tare two types of subjects in the examined range in both of the systems: investors and other subjects), character of technological connections. The following are classed in the second group of features: preferences of subjects (either maximization of a ratio of investments to effects or vice versa), character of disequilibrium (demand or supply) and a type of disequilibrium asymmetry (from the beginning to the end of technological course and reverse). The study of a course of business cycle is presented with the use of numerical model with several simplifying assumptions being made. Beginning of a cycle, in both of the systems is marked by ridding of bottle-necks performed in capitalism by means of investments in branches producing final consumption, goods, and in sociailism by investments In branches developing resources. Thai; initial impuis effects expansion of production capacities in those branches which respectively become bottle necks of economy. Sequence of investments fin socialism is reverse to the one of capitalism. Both systems enter their optimum stages where unutilization of productive powers effected by existence of bottle necks is lowest, in economy treated as a whole. Further development, forced by internal mechanisms results in a return to the initial stage of structural disequilibrium. The article contributes also several more general reflections concerning development perspectives of comparative economy.
Comparative analysis of economic cycles in capitalism and socialism